DETERMINATION OF ANTIMICROBIAL ACTIVITY OF EXTRACTS OF CALENDULA OFFICINALIS FLOWERS - P. V. Afanasyeva; A. V. Kurkina; V. A. Kurkin; A. V. Lyamin; A. V. Zhestkov (Фармация и фармакология (Пятигорск))
Pot marigold (Calendula officinalis L.) is one of the most popular medicinal plants in the Russian Federation and abroad. The wide range of pharmacological activity of this medicinal plant is determined by carotenoids, flavonoids, saponins. These biologically active substances give total therapeutic effect of flowers of Calendula officinalis and medicines on base of pot marigold. This paper discusses the results of comparative investigations for a determination of antimicrobial activity of aqueous and aqueous- alcoholic extracts from pot marigold flowers. Detection of the minimum inhibitory concentration (MIC) was carried out by using the method of double serial dilutions in broth. The following microorganisms were used as test cultures: Bacillus cereus, Candida albicans, Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus. The study showed that the widest spectrum of antibacterial activity has water extract of pot marigold flowers. As for Pseudomonas aeruginosa the most active medicine is tincture (1:10) with 70% alcohol. As for Escherichia coli the only phytopharmaceutical – water extract of marigold flowers, reveals antimicrobial activity. Against Bacillus cereus the most effective properties was indicated for tincture (1:5) with 70% ethanol and the liquid extract (1:2) with 70% alcohol. In case of Candida albicans, tincture (1:10) with 70% alcohol exhibited the highest activity.